The Use of Military Metaphor in Cancer Conversations - O'Sullivan, Emma; Adams, Niamh; OBoyle, Colm (My University, 2020)
Poster presenting systematic review of metaphor use in end of life care
Trinity Health and Education International Research Conference 2020 (THEconf2020): ?Integrated healthcare: developing person-centred health systems?
Keywords: End-of-life; Metaphor; Cancer care